2003
DOI: 10.1029/2001jb000818
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative shape measurements of distal volcanic ash

Abstract: [1] Large-scale volcanic eruptions produce fine ash (<200 mm) which has a long atmospheric residence time (1 hour or more) and can be transported great distances from the volcanic source, thus, becoming a hazard to aircraft and public health. Ash particles have irregular shapes, so data on particle shape, size, and terminal velocities are needed to understand how the irregular-shaped particles affect transport processes and radiative transfer measurements. In this study, a methodology was developed to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
168
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 36 publications
(71 reference statements)
8
168
1
1
Order By: Relevance
“…In previous studies of volcanic ash, in-situ devices and remote sensing techniques were demonstrated to be the most powerful tools for quantitative measurements of its presence (Pieri et al, 2002;Sassen et al, 2007;Delene et al, 1996). Furthermore, in the case of in-situ measurements, the morphology and chemical composition of the volcanic ash can simultaneously be analyzed (Riley et al, 2003;Taylor and Lichte, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of volcanic ash, in-situ devices and remote sensing techniques were demonstrated to be the most powerful tools for quantitative measurements of its presence (Pieri et al, 2002;Sassen et al, 2007;Delene et al, 1996). Furthermore, in the case of in-situ measurements, the morphology and chemical composition of the volcanic ash can simultaneously be analyzed (Riley et al, 2003;Taylor and Lichte, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Eiríksson et al, 1994;Dellino and La Volpe, 1996;Carey, 2002, 2007;Riley et al, 2003;Shea et al, 2010). These methods, however, provide only incomplete shape descriptors, due to the inherent limitations of 2D techniques to fully retrieve 3D features (Baker et al, 2012).…”
Section: Introduction and Previous Workmentioning
confidence: 99%
“…In terms of aerodynamics, shape has a direct impact on the drag forces acting on rising and falling particles (Stringham et al, 1969;Bursik, 1989;Ganser, 1993;Mitchell, 1996;Chhabra et al, 1999;Mele et al, 2011;Dellino et al, 2012), which in turn influence the settling velocity (Wilson and Huang, 1979;Coltelli et al, 2008;Alfano et al, 2011), the atmospheric residence time (Riley et al, 2003), and the transport distance and dispersal of tephra (Sparks et al, 1997;Scollo et al, 2008). The aerial behavior of ash is also indirectly influenced by the surface-to-volume ratio, which affects the propensity of particles to form aggregates, both in dry and wet environments (e.g.…”
Section: Introduction and Previous Workmentioning
confidence: 99%
“…From a microscopic perspective, the relation between particle morphology and eruptive and transport mechanisms has been abundantly explored (e.g., Dellino and Liotino 2002;Ersoy et al 2006Ersoy et al , 2008Heiken and Wohletz 1985;Leibrandt and Le Pennec 2015;Liu et al 2015;Rausch et al 2015;Riley et al 2003;Sheridan and Kortemeier 1987;Sheridan and Marshall 1983;Vonlanthen et al 2015). Heiken (1972) considered that the shape of particles in the ash size range is mostly dependent on the shape of magmatic gas bubbles at the moment of fragmentation: flat and platy shards arise from broken vesicle walls, and droplet shapes are produced from low viscosity magma where the effect of surface tension is likely to become more important.…”
Section: Introductionmentioning
confidence: 99%